Combined Long-Term Androgen Deprivation and Pelvic Radiotherapy in the Post-operative Management of Pathologically Defined High-Risk Prostate Cancer Patients: Results of the Prospective Phase II McGill 0913 Study - Kucharczyk, Michael Jonathan; Tsui, James Man Git; Khosrow-Khavar, Farzin; Bahoric, Boris; Souhami, Luis; Anidjar, Maurice; Probst, Stephan; Chaddad, Ahmad; Sargos, Paul; Niazi, Tamim (Frontiers in Oncology, 2020)
Purpose: Following radical prostatectomy, prostate bed radiotherapy (PBRT) has been combined with either long-term androgen deprivation therapy (LT-ADT) or short-term ADT with pelvic lymph node radiotherapy (PLNRT) to provide an oncological benefit in randomized trials. McGill 0913 was designed to characterize the efficacy of combining PBRT, PLNRT, and LT-ADT. It is the first study to do so prospectively. Methods: In a single arm phase II trial conduced from 2010 to 2016, 46 post-prostatectomy prostate cancer patients at a high-risk for relapse (pathological Gleason 8+ or T3) were assessed for treatment with combined LT-ADT (24 months), PBRT, and PLNRT. Patients received PLNRT and PBRT (44 Gy in 22 fractions) followed by a PBRT boost (22 Gy in 11 fractions). The primary endpoint was progression-free survival (PFS). Toxicity and quality of life (QoL) were evaluated using CTCAE V3.0 and EQ-5D-3L questionnaires, respectively. Results: Among the 43 patients were treated as per protocol, median PSA was 0.30 µg/L. On surgical pathology, 51% had positive margins, 40% had Gleason 8+ disease, 42% had seminal vesicle involvement, and 19% had lymph node involvement. At a median follow-up of 5.2 years, there were no deaths or clinical progression. At 5 years, PFS was 78.0% (95% Confidence Interval 63.7%-95.5%). Not including erectile dysfunction, patients experienced: 14% grade 2 endocrine toxicity while on ADT, one incident of long-term gynecomastia, 5% grade 2 acute urinary toxicity, 5% grade 2 late urinary toxicity, and 24% long-term hypogonadism. No comparison between the average or minimum self-reported QoL at baseline, during ADT, nor after ADT demonstrated a statistically significant difference. Conclusions: Combining PBRT, PLNRT, and LT-ADT had an acceptable PFS in patients with significant post-operative risk factors for recurrence. While therapy was well tolerated, long-term hypogonadism was a substantial risk. Further investigations are needed to determine if this combination is beneficial. Trial registration: NCT01255891